Evaluation of the restricted virtual space approximation in the algebraic-diagrammatic construction scheme for the polarization propagator to speed-up excited-state calculations - Yang, Chong; Dreuw, Andreas (Journal of computational chemistry, 2017)
The applicability and limitations of the restricted virtual space (RVS) approximation within the algebraic-diagrammatic construction (ADC) scheme for the polarization propagator up to third order is evaluated. In RVS-ADC, not only the core but also a substantial amount of energetically high-lying virtual orbitals is restricted in excitation energy calculations of low-lying excited electronic states. Using octatetraene, indole, and pyridine as representative examples and different standard basis sets of triple-zeta quality, RVS-ADC(2) turns out to be highly useful and to have negligible effects on ππ* excited states. However, for nπ* or πσ* states, the RVS approximation is generally less reliable but better at third-order than second-order ADC level. In addition, a unified, basis-set independent, thus normalized virtual orbital threshold (value) is introduced, making the RVS approximation more controllable and a priori applicable.